2020
DOI: 10.1039/c9bm01207a
|View full text |Cite
|
Sign up to set email alerts
|

The fabrication of a highly efficient self-healing hydrogel from natural biopolymers loaded with exosomes for the synergistic promotion of severe wound healing

Abstract: Highly efficient self-healing hydrogels from natural biopolymers loaded with exosome biological nanoparticles for the synergistic promotion of severe wound healing are demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
94
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(95 citation statements)
references
References 40 publications
0
94
0
1
Order By: Relevance
“…They immobilized the bone-forming peptides-1 (BFP-1) using this technique, which allowed a slow release of BFP-1 and showed that combining hASCs and PLGA/pDA can enhance bone formation [ 64 ]. Most recently, Wang et al described a highly efficient injectable self-healing hydrogel fabrication using a Schiff base linkage for applications in severe wound healing [ 61 ]. They constructed a methyl-cellulose (MC)–chitosan (CS) combination of a hydrogel with placental cell-derived exosomes.…”
Section: Exosomes and Hydrogelsmentioning
confidence: 99%
See 1 more Smart Citation
“…They immobilized the bone-forming peptides-1 (BFP-1) using this technique, which allowed a slow release of BFP-1 and showed that combining hASCs and PLGA/pDA can enhance bone formation [ 64 ]. Most recently, Wang et al described a highly efficient injectable self-healing hydrogel fabrication using a Schiff base linkage for applications in severe wound healing [ 61 ]. They constructed a methyl-cellulose (MC)–chitosan (CS) combination of a hydrogel with placental cell-derived exosomes.…”
Section: Exosomes and Hydrogelsmentioning
confidence: 99%
“…The MC- and CS-grafted polyethylene glycol were synthesized using DCC (dicyclohexyl- carbodiimide) and EDC (1-(3-dimethylaminopropyl)-3-ethylcarbodiimide) reactions. Both these polymer solutions were mixed together along with exosomes to fabricate the complex hydrogel [ 61 ].…”
Section: Exosomes and Hydrogelsmentioning
confidence: 99%
“…Rapid and robust self-healing properties were demonstrated by the hydrogels obtained by Schiff-base reactions between aldehyde groups of modified methyl cellulose and the amine groups of PEG-grafted chitosan. The gels were explored as scaffolds for the loading of exosomes and this combination led to a synergistic improvement of their wound healing ability [ 128 ].…”
Section: Tissue Engineering Applicationsmentioning
confidence: 99%
“…Ce travail démontre une nouvelle approche pour augmenter la livraison du traitement de l'infarctus du myocarde. Liu et al ont rapporté que le chargement d'EV avec un nouveau complexe d'hydrogels peut favoriser la cicatrisation des plaies, ce qui fournit une autre stratégie d'hydrogel efficace pour l'ingénierie des EV 7 . Li et al ont étudié les rôles d'Exo-pGel dans le traitement des lésions de la moelle épinière.…”
Section: Techniques D'ingenierie Artificielle Des Vési-cules Et Des Nunclassified